Empowerment of Young Entrepreneurs Based on Majelis Ta'lim in Neroktog Village Through Design, Screen Printing, and Digital Marketing Training - Erianti, Een; Hardiyanti, Rini; Pradesti, Ajeng; Suseno, Ari; Yesika; Dyland, Glend (Jurnal Pengabdian Masyarakat, 2024)
Purpose: This community service program aims to empower young people by promoting entrepreneurship and enhancing their skills, particularly in response to high unemployment and the economic impact of the COVID-19 pandemic. The goal is to produce young entrepreneurs who can drive local economic growth.Method: The program includes seminars, workshops, and mentorship in digital marketing, product branding, and entrepreneurial management. It follows a structured process from planning to evaluation, with pre- and post-assessments to measure participant progress.Practical Applications: The program equips participants with skills to leverage digital platforms for business growth, helping them address unemployment and social issues by becoming self-reliant entrepreneurs.Conclusion: The program shows that building entrepreneurial and digital marketing skills boosts young people's productivity and economic potential, contributing to local development and addressing social challenges.